Acteoside attenuates RSV-induced lung injury by suppressing necroptosis and regulating metabolism - Ling, Xiaoying; Zhou, Jie; Jin, Tianzi; Xu, Weichen; Sun, Xun; Li, Weifeng; Ding, Yali; Liang, Miaomiao; Zhu, Chenbi; Zhao, Peipei; Hu, Chanchan; Yuan, Bin; et al. (Frontiers in Pharmacology, 2022)
Background: Necroptosis and inflammation are closely related to the pathogenesis of respiratory syncytial virus (RSV). Acteoside (AC), a natural phenylpropanoid glycoside from Kuding Tea, has significant anti-RSV effect. However, the roles of AC on RSV-induced lung necroptosis and inflammation are yet to be elucidated. Methods: The effects of AC were investigated in BALB/c mice and A549 cells. Lung histopathology was observed through H&E staining. The viral titer was assessed via plaque assay. The RSV-F expression was determined by RT-qPCR and immunohistochemistry assay. The levels of cytokines were detected by ELISA and RT-qPCR. The necroptosis rate and mitochondrial membrane potential were evaluated via flow cytometry. The expressions of HMGB1/NF-κB and RIP1/RIP3/MLKL/PGAM5/DRP1 were detected by western blot. Additionally, untargeted metabolomics was conducted to investigate the metabolic profiles and related metabolic pathways via Gas Chromatography-Mass Spectrometry. Results: The results showed that compared with the RSV-infected group, AC treatment significantly attenuated lung pathological damage, virus replication, and cytokines levels. AC also alleviated RSV-induced necroptosis and mitochondrial dysfunction in vitro and in vivo. Moreover, AC treatment down-regulated the expression of HMGB1, p-Iκbα/Iκbα, p-p65/p65, RIP1, RIP3, MLKL, PGAM5, and DRP1. Furthermore, metabolomic analyses suggested that the perturbations in major metabolites of AC therapy were related to variations in amino acid and energy metabolism. Conclusion: Our findings validated the beneficial effects of AC in suppressing necroptosis and regulating metabolism, suggesting AC may be a new drug candidate for RSV infection.